Non-syndrome multiple supplemental supernumerary teeth - Kalra N; Chaudhary S; Sanghi S (Wolters Kluwer Medknow Publications, 2005)
Multiple supernumerary teeth without any associated systemic conditions or syndromes are not common. We document a case of non-syndrome multiple supplemental supernumerary teeth in mandibular premolar region of an adolescent male patient, an incidental findings during routine radiographic examination. Periodic examination is recommended to monitor the clinical behavior.